Praktek Gadai Emas pada PT Bank Syariah Mandiri Ternate - Rusandry Rusandry (Jurnal Ilmiah Wahana Pendidikan, 2021)
The prevalence of gold pawning practices, there are many indications that gold is an item that has a certain electrical value where the value of the item fluctuates rapidly compared to other goods. This has become a debate so that it has become a contemporary problem which is still being discussed today, therefore gold pawning is very worthy of further study. One of the banks that is the object of discussion on gold pawning is Bank Syariah Mandiri with the pawn concept offered by PT Bank Syariah Mandiri using the Qardh wal Ijarah contract.